2013
DOI: 10.1002/ange.201305492
|View full text |Cite
|
Sign up to set email alerts
|

A Powerful Hydrogen‐Bond‐Donating Organocatalyst for the Enantioselective Intramolecular Oxa‐Michael Reaction of α,β‐Unsaturated Amides and Esters

Abstract: Die Einstellung des Organokatalysators ist entscheidend: Unter Verwendung eines Wasserstoffbrückendonors als Organokatalysator wurde eine neuartige enantioselektive intramolekulare Oxa‐Michael‐Reaktion nicht aktivierter α,β‐ungesättigter Amide und Ester entwickelt. Zusätzlich konnten die hierbei erhaltenen Produkte für die asymmetrische Synthese einiger Naturstoffe und biologisch wichtiger Verbindungen verwendet werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…[14,15] Nevertheless,o vercoming the direct conjugate addition of peroxide on an a,b-unsaturated moiety remains apotential barrier to this strategy. [16] Further, both enantioselective acetalization [15,17] and oxa-Michael reactions [18][19][20][21] are challenging tasks because of their inherent reversibility.Herein we report the very first synthesis of exoperoxyacetals (C)inexcellent enantio-and diastereoselectivity,t hus providing the sterically hindered cis-stereoisomer. Furthermore,i tc an also be converted into the trans-stereoisomer D by as imple acid-catalyzed process without loss in enantioselectivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15] Nevertheless,o vercoming the direct conjugate addition of peroxide on an a,b-unsaturated moiety remains apotential barrier to this strategy. [16] Further, both enantioselective acetalization [15,17] and oxa-Michael reactions [18][19][20][21] are challenging tasks because of their inherent reversibility.Herein we report the very first synthesis of exoperoxyacetals (C)inexcellent enantio-and diastereoselectivity,t hus providing the sterically hindered cis-stereoisomer. Furthermore,i tc an also be converted into the trans-stereoisomer D by as imple acid-catalyzed process without loss in enantioselectivity.…”
mentioning
confidence: 99%
“…Subsequently,o xidation of ah ydroxy into ac arbonyl functionality provides the chiral isocoumarine core 13.A nd the corresponding aliphatic peroxy-tetrahydrofurans 7a-c could be ap otential substrate for enantiopure g-lactones.T he absolute stereochemistry of 9 was confirmed by the correlation with the literature value. [21b] To explain the observed absolute stereochemical outcome,ab ifunctional mechanism similar to those previously proposed for the squaramide/thiourea-catalyzed oxa/aza-Michael reaction of enones [15,[19][20][21] may be invoked (Scheme 7). The re-face of the enone in either TS-1 or TS-2 is in perfect alignment to drive the formation of the product with the desired stereochemistry.Asshown in TS-1,the OOR group at the b-position imposes as teric hindrance with the bicyclics keleton of the catalyst, thus prohibiting the interaction of the catalyst with the substrate.Whereas,inTS-2 the OOR group is situated away from the bicyclics keleton, and thus does not hinder the catalyst-substrate association.…”
mentioning
confidence: 99%
“…[9][10] Previously, we reported that a cascade reaction with aldehydes and β,γunsaturated α-ketoesters, using modularly designed organocatalysts as catalytic system, [11] which proceeded smoothly to get both enantiomers of cis-and transfused pyrano [2,3-b]pyran derivatives. [12] Inspired by those elegant works, we herein described a concise construction of fused tricyclic pyrano-pyrano-pyrrol through a highly enantioselective Michael additionacetalation [13] /oxa-Michael [14] reaction of dioxopyrrolidines [10] with aldehydes using modularly designed organocatalysts.…”
mentioning
confidence: 99%